The everyday political economy of Southeast Asia - Elias, Juanita; Rethel, Lena (Cambridge : Cambridge University Press, 2016)
In this empirically rich collection of essays, a team of leading international scholars explore the way that economic transformation is sustained and challenged by everyday practices across Southeast Asia. Drawing together a body of interdisciplinary scholarship, the authors explore how the emergence of more marketized forms of economic policy-making in Southeast Asia impacts everyday life. The book's twelve chapters address topics such as domestic migration, trade union politics in Myanmar, mining in the Philippines, halal food in Singapore, Islamic finance in Malaysia, education reform in Indonesia, street vending in Malaysia, regional migration between Malaysia, Indonesia and Cambodia, and Southeast Asian domestic workers in Hong Kong. This collection not only enhances understandings of the everyday political economies at work in specific Southeast Asian sites, but makes a major theoretical contribution to the development of an everyday political economy approach in which perspectives from developing economies and non-Western actors are taken seriously.
Southeast Asia and everyday political economy / Juanita Elias and Lena Rethel -- From development to multiple modernities -- Policies and negotiated everyday living: a view from the margins of development in Thailand and Vietnam / Johnathan Rigg -- Everyday agents of change: trade unions in Myanmar / Jewellord T. Nem Singh and Alvin A. Camba -- Neoliberalism, resource governance and the everyday politics of protest in the Philippines: everyday agents of change: trade unions in Myanmar / Nicholas Henry -- Widening and deepening markets -- The political economy of Muslim markets in Singapore / Johan Fischer -- Islamic finance in Malaysia: global ambitions, local realities / Lena Rethel -- Resisting marketization: everyday actors, courts and education reform in post-new order Indonesia / Andrew Rosser -- People, mobilities and work -- From formal employment to street vending: Malaysian women's labour force participation over the life course / Anja K. Franck -- Everyday identities in motion: situating Malaysians within the'war for talent' / Adam Tyson -- Regional disputes over the transnationalization of domestic labour: Malaysia's'maid shortage' and foreign relations with Indonesia and Cambodia / Juanita Elias and Jonathan Louth -- Everyday agency, resistance and community resources for Indonesian migrant workers in Hong Kong / Carol G. S. Tan -- Conclusion -- Everyday international political economy meets the everyday political economy of Southeast Asia / john M. Hobson, Juanita Elias, Lena Rethel and Leonard Seabrooke.
Title from publisher's bibliographic system (viewed on 08 Aug 2016).
Keywords: Southeast Asia -- Economic conditions; Economic development -- Social aspects -- Southeast Asia